Optimal Routing Control in Disconnected Machine-to-Machine Networks. (16th August 2012) - Wu, Yahui; Deng, Su; Huang, Hongbin
Abstract : Machine-to-machine (M2M) networks could be connected by a wide range of wireless technologies (e.g., Bluetooth, WiFi, RFID). Due to some factors (e.g., mobility of machines, limited communication range), it is hard to maintain the connectivity of the network, that is, the network is disconnected and it is a specific application of delay tolerant networks (DTN). Communication in such network often needs nodes working in a cooperative way. However, due to selfishness, nodes have no incentive to help others. Therefore, if the source requests help from other nodes, it needs to pay certain fees to them. The main goal of this paper is to explore efficient ways for the source to maximize the average delivery ratio when the total fees are limited. First, we mathematically characterize the average delivery ratio under different policies. Then we get the optimal policy through Pontryagin's maximum principle, and prove that the optimal policy conforms to the threshold form when the fees that other nodes require satisfy certain conditions. Simulations based on both synthetic and real motion traces show the accuracy of our model. Through extensive numerical results, we demonstrate that the optimal policy obtained by our model is the best.